2015
DOI: 10.1115/1.4030881
|View full text |Cite
|
Sign up to set email alerts
|

Shape Bifurcation of a Spherical Dielectric Elastomer Balloon Under the Actions of Internal Pressure and Electric Voltage

Abstract: Under the actions of internal pressure and electric voltage, a spherical dielectric elastomer balloon usually keeps a sphere during its deformation, which has also been assumed in many previous studies. In this article, using linear perturbation analysis, we demonstrate that a spherical dielectric elastomer balloon may bifurcate to a non-spherical shape under certain electromechanical loading conditions. We also show that with a non-spherical shape, the dielectric elastomer balloon may have highly inhomogeneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…Localized electromechanical instabilities were demonstrated by observing voltage-induced wrinkling in a DE strip (Park et al, 2012) and an inflated DE balloon (Mao et al, 2015). A spherical DE balloon under internal pressure and electric voltage has been analyzed, with results showing that inhomogeneous viscoelastic deformation may cause timedependent failure modes (Wang H. et al, 2013), and bifurcation to a non-spherical shape may occur under certain electromechanical loading conditions (Liang and Cai, 2015). …”
Section: Influence Of Pre-stretch On De Performancementioning
confidence: 99%
“…Localized electromechanical instabilities were demonstrated by observing voltage-induced wrinkling in a DE strip (Park et al, 2012) and an inflated DE balloon (Mao et al, 2015). A spherical DE balloon under internal pressure and electric voltage has been analyzed, with results showing that inhomogeneous viscoelastic deformation may cause timedependent failure modes (Wang H. et al, 2013), and bifurcation to a non-spherical shape may occur under certain electromechanical loading conditions (Liang and Cai, 2015). …”
Section: Influence Of Pre-stretch On De Performancementioning
confidence: 99%
“…However, it is noted that bifurcation instability may occur for a Mooney material subject to a voltage (Diaz-Calleja et al, 2009); a non-spherical shell can be found in the current configuration. Liang and Cai (2015) found a highly inhomogeneous electric field and stress/stretch distributions with a non-spherical shape and studied the stability analysis of a DE balloon in different equilibrium configurations. For a non-spherical configuration, the dynamical behavior will be more complicated.…”
Section: Theoretical Workmentioning
confidence: 99%
“…A shooting method was adopted by Fu and Xie [16] to numerically solve Eq. (6), while a linear perturbation analysis was performed by Liang and Cai [21] to calculate critical conditions of Eq. (6).…”
Section: Spherical Balloon ( ∕ = 1)mentioning
confidence: 99%
“…Beyond the pure mechanical loading, the inflation of balloons under an electromechanical coupling field has been taken into account [17][18][19][20]. Liang and Cai [21] conducted a linear perturbation analysis on the spherical dielectric elastomer balloon under the actions of internal pressure and electric voltage, and revealed that the pear-shaped deformation becomes more obvious due to the contribution of electric field.…”
Section: Introductionmentioning
confidence: 99%